The value gap : female-driven films from pitch to premiere - Brannon Donoghue, Courtney (Tantor Media, Inc., 2023)
"Conversations about gender equity in the workplace accelerated in the 2010s, with debates inside Hollywood specifically pointing to broader systemic problems of employment disparities and exploitative labor practices. Compounded by the devastating #MeToo revelations, these problems led to a wide-scale call for change. The Value Gap traces female-driven filmmaking across development, financing, production, film festivals, marketing, and distribution, examining the realities facing women working in the industry during this transformative moment. Drawing from five years of extensive interviews with female producers, writers, and directors at different stages of their careers, Courtney Brannon Donoghue examines how Hollywood business cultures ""value"" female-driven projects as risky or not bankable. Industry claims that ""movies targeting female audiences don't make money"" or ""women can't direct big-budget blockbusters"" have long circulated to rationalize systemic gender inequities and have served to normalize studios prioritizing the white male-driven status quo. Through a critical media industry studies lens, The Value Gap challenges this pervasive logic with firsthand accounts of women actively navigating the male-dominated and conglomerate-owned industrial landscape."